CITRA IBU PADA PUISI: DALAM PENGEMBARAAN PENYAIR INDONESIA - Abdul Aziz Rasjid (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
This article directed to study mother imagination through poem that produced by Indonesian poets on their wandering toâ€œculture migrationâ€ cities. The cause is the rise of nationalism and modernism ideas that established new belief that human as â€œcenter ofcreativityâ€. Mother image is son perspective to his mother and this perspective poet is that write mother on his poem. Poem about mothertaken from 1930 to 1998 that used as interpretation object to reveal poetâ€™s sub-consciousness realm to obtain knowledge about son imageto his mother on Indonesian poem history and this nation history (colonialism, independence, economic-politic turbulence, till reformation).Through poem, researcher also analyze if there is a gender bias on this mother image